General Equilibrium Modeling for Economic Policy Analysis - Trinh, Truong Hong (International Journal of Economics and Financial Issues, 2019)
This paper explores the value concept that is important in determining the relationship between demand and supply, and resource allocation in the economy. From value creation perspective, the value concept is redefined to explain value creation and value distribution in the economy. Based on this value concept, the value added method is used for gross domestic product (GDP) measurement that is also used as the objective function in the general equilibrium model. The starting point in general equilibrium modeling is the understanding on the structure and the flows of the economy, in which the general equilibrium mechanism relies on market equilibriums and macro balances. The simulation experiment is used to conduct economic policies from the changes in target sector structure and the combinations of macro closures in the hypothetical economy. The paper contributes a conceptual framework in general equilibrium modeling for economic policy analysis as a good start to understand the more complex general equilibrium models. Keywords: value concept, market equilibrium, general equilibrium, policy analysis, economic growth JEL Classifications: C60; D46; D58; O20 DOI: https://doi.org/10.32479/ijefi.8164